Spatial inequality of dental caries in the Brazilian territory - Rayanne Karina Silva Cruz; Yan Nogueira Leite de Freitas; Tamires Carneiro de Oliveira Mendes; Janmille Valdivino da Silva; Flávia Christiane de Azevedo Machado; Maisa Paulino Rodrigues; Maria Angela Fernandes Ferreira (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: The distribution of harms to health varies spatially determined by the socioeconomic conditions of the environment. This research aimed to assess the spatial distribution of dental caries in 12-year-old children and their correlation with socioeconomic indicators in Brazilian states. The sample of this ecological study comprised all the 26 Brazilian states and the Federal District. Thematic and correlation maps were constructed in order to assess the spatial dependency, as well as the correlation between dental caries and socioeconomic factors. The results showed that the states with the worst DMFT indexes were located in the north and northeast, showing spatial autocorrelation. These regions also had the worst results for the following variables: poverty, illiteracy, education, and income. The bivariate analysis showed that household income and education level had negative spatial correlation with the DMFT index, while illiteracy and poverty rates showed positive correlation. Despite advances in the decline of DMFT index in recent years, there is still an inequity in the distribution of the caries disease.